The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/scs.0000000000003328
|View full text |Cite
|
Sign up to set email alerts
|

Modified Superior-Based Pharyngeal Flap Is Effective in Treatment of Velopharyngeal Insufficiency Regardless of the Preoperative Closure Pattern

Abstract: Velopharyngeal insufficiency (VPI) is certainly one of the most important problems confronted after cleft palate repairs. In this study, it was aimed to evaluate the preoperative and postoperative speaking results of patients who underwent modified superior-based pharyngeal flap. Sixty-six children who underwent modified superiorly based pharyngeal flap for treatment of VPI between 2005 and 2013 were retrospectively reviewed. The study population was evaluated in 2 distinctive groups depending on their preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…However, in this study, we did not find any association between closure pattern and successful outcome. The similar reports presented by Ekin et al (2017) indicated no significant difference between the preoperative and postoperative results in terms of the mean closure pattern after the surgical approach using a modified superior-based pharyngeal flap for VPI in 66 children. Finally, there were no patients with sagittal closure pattern in this study.…”
Section: Discussionsupporting
confidence: 60%
“…However, in this study, we did not find any association between closure pattern and successful outcome. The similar reports presented by Ekin et al (2017) indicated no significant difference between the preoperative and postoperative results in terms of the mean closure pattern after the surgical approach using a modified superior-based pharyngeal flap for VPI in 66 children. Finally, there were no patients with sagittal closure pattern in this study.…”
Section: Discussionsupporting
confidence: 60%
“…Among the surgical techniques described in the literature for the treatment of velopharyngeal dysfunction, pharyngeal flap surgery with superior pedicle still presents high success rates concerning the elimination of speech symptoms (7,(21)(22)(23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…A flexible fiberoptic endoscope was inserted for evaluation of velopharyngeal motility and visualization of the anatomy under various conditions and phonations. VPI was evaluated by closure of the velopharyngeal port during phonation [ 15 ]. To determine the surgical plan preoperatively, or to evaluate postoperative outcomes, the size of the central gap was measured with the lateral pharyngeal walls maximally contracted to the velopharyngeal port.…”
Section: Methodsmentioning
confidence: 99%
“…LITE is a modified two-flap palatoplasty that limits the incision at the anterior hard palate and elevates the movable palatal flap with thorough dissection over the entire palate [13]. DOZ or LITE was considered to be ineffective when the results of speech evaluation and nasopharyngoscopy showed that the palatal muscle was incompetent, and PPF was performed to create an anatomical barrier between the oral cavity and the nasal cavity to reduce nasal emission [15]. The PPF procedure involves elevation of a superior-based myomucosal flap and insertion into the soft palate to create a static sling and overcome the VPI.…”
Section: Palatoplasty Methodsmentioning
confidence: 99%